PEMILIHAN FOOD OUTLET SEBAGAI FAKTOR RESIKO BERAT BADAN LEBIH ANAK USIA SEKOLAH DASAR DI KECAMATAN TEGALSARI SURABAYA - , RENNY EVELYN HARTONO, Dr.rer.nat.dr. BJ. Istiti Kandarina ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Introduction: Overweight and obesity is a condition resulting from an imbalance of calories in the body that occur in a long time and causes more deaths than underweight. One of factor that is directly related is food pattern, which also influenced the selection of food outlets. Surabaya is an urban area so it has many type and characteristic of food outlet. Elementary children (4th, 5th, 6th) has been not too dependent on their parents, so their food consumption and physical activity began to vary. Objection: To identify the relationship between the selection of food outlets and overweight/ obesity status of children elementary children in the Tegalsari district, Surabaya. Methods: Research using a case-control study design. The samples were 51 children for each group of cases and control and obtained from 11 primary school in the 5 subdistrict in Tegalsari district, Surabaya. Data obtained by interview, direct observation to food outlets and interviews to selected informants about the reasons for the selection of food outlets. Quantitative data processed by bivariate (chi-square) and multivariate (binomial regression) test. Result: Bivariate test results gained significant relationship exists between the frequency to the street vendors (OR=4,09